The Impact of Environmental Changes Caused by Earthquake Toward Emotional Problems of Preschool Children - Triana, Vivi (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Natural disasters can result in death and disability that lead to loss, grief and emotional disturbance reactions. The disorder is more common in children underwent development period. Neurological changes in children who experience Post Traumatic Syndrome Disorder (PTSD) 1.5 times greater than in adults. This study aims to determine the impact of environmental changes caused by the earthquake in Padang Pariaman district towards emotional problems of children aged 3-5 years. We used retrospective cohort study design in a population of children aged 3-5 years in September 2009. The sample was 219 people who were taken using stratified random sampling method. Data was collected by interviewing the parents through a questionnaire and analyzed using univariate and bivariate analysis. We observed a significant relationship between environment damage (p= 0.017), occupation (p= 0.02) and economic status (p= 0.03) with emotional problems in children. Education did not have a significant relationship with emotional problems in children.